Examining the role of employee engagement in the relationship between organisational cynicism and employee performance. Issue 1 (11th March 2019) - Arslan, Muhammad; Roudaki, Jamal
Abstract : Purpose: Organisational cynicism (OC) is a growing trend in contemporary organisations. However, its impact on employee performance (EP) remains understudied. The purpose of this paper is to address this gap by investigating its effect on EP. The study also investigates the moderating effect of employee engagement (EE) on the relationship between OC and EP. Design/methodology/approach: Primary data are collected through questionnaire from employees ( N =200) of various health organisations in Pakistan by employing a convenient sampling technique. Hierarchical multiple regression is employed by using SPSS. Findings: The findings of correlation and regression analyses reveal that OC has significant negative relationship with EP. Hence, the patient care is compromised in sampled organisations due to poorer performance of employees. Moreover, findings also reveal that EE has a moderating effect on relationship between OC and EP. Therefore, hospital management needs to increase EE to reduce the cynicism and improve performance. In addition, organisations and managers need to consider their role and actions creating the conditions that lead to cynicism among employees and should take trustworthy steps to increase employee retention and engagement and, ultimately, their performance. Moreover, the findings of the study indicate that the majority of respondents are not happy with their organisations. They also feel that the organisation is not fulfilling its promises and betraying them in several ways. This breach of contract becomes the reason for OC among employees and badly affects their performance. Most of respondents give importance to their career development and the findings reveal that organisations are not focussing on career development of their employees. Research limitations/implications: The study has some limitations and implications. The organisational culture can mitigate the negative effect of OC and enhance performance by promoting EE. It is recommended that employee cynicism can be reduced by providing a supportive environment, EE and fairness. Nevertheless, the findings of this study still help supervisors to inhibit this harmful effect by reducing the level of psychological contract violation and organisational politics that will reduce the level of cynicism among employees and improve their performance. Practical implications: It is found that OC has a major impact on the behaviour and attitude of employees, supervisors and representatives on the one hand and, ultimately, the organisation, on the other hand. These effects have specific susceptibilities due to the vicinity of the employees. It is recommended that employee cynicism can be reduced by providing a supportive environment. Social implications: The study also helps psychologists to understand employees' attitudes and improve personnel selection to ensure they recruit the right people. Leaders need to communicate honestly, effectively and frequently to address cynicism in order to ensure ample staffing and resource levels that result in good patient care and positive work attitudes at hospitals. Originality/value: According to the researchers' best knowledge, only few studies tried to investigate the relationship between organisational cynicism and EP by employing the moderating effect of EE. Therefore, it will be a good contribution in existing literature to understand consequences of cynicisms.